1997
DOI: 10.1002/(sici)1097-0142(19970415)79:8<1600::aid-cncr24>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Bladder carcinoma and other second malignancies after radiotherapy for prostate carcinoma

Abstract: carcinoma was elevated for the RT group (RR 1.5; 95% confidence interval [CI], Medical Center, Haifa, Israel.1.1-2.0) but not for the non-RT group (RR 1.0; 95% CI, 0.7-1.2). R adiation therapy (RT) is known to cause a variety of malignancies, including leukemia, sarcomas, thyroid carcinoma, and lung carcinoma.1-3 Scattered reports have suggested links to other malignancies, such as gastric carcinoma, as well.2 As would be expected, the organs at risk for a given type of RT are the sites that lie within the rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
109
1
6

Year Published

1997
1997
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(125 citation statements)
references
References 16 publications
9
109
1
6
Order By: Relevance
“…23 BC tends to occur 5 to 10 years after radiation and is characteristically high grade and locally advanced at diagnosis. 24 The relative risk of secondary bladder malignancy ranges 1.5-to 4-fold and is likely proportional to the dose of radiation given.…”
Section: Cyclophosphamidementioning
confidence: 99%
“…23 BC tends to occur 5 to 10 years after radiation and is characteristically high grade and locally advanced at diagnosis. 24 The relative risk of secondary bladder malignancy ranges 1.5-to 4-fold and is likely proportional to the dose of radiation given.…”
Section: Cyclophosphamidementioning
confidence: 99%
“…Moreover, the relatively short follow-up (ie, 42.3 months) of these patients highlights these results, excluding a confounding action of RT in the development of secondary primaries. [49][50][51] Obese men may need more extensive staging and closer follow-up to detect subsequent new malignancies. There are inherent limitations in this study that are important to underline.…”
Section: Discussionmentioning
confidence: 99%
“…9 Whether radiotherapy increases bladder cancer risk remains a subject of continued debate. 8,[10][11][12][13][14][15][16][17][18][27][28][29] The consequences of radiation exposure vary in different animals and even different strains of the same species, and in organs within a species. 23 The development of secondary cancer may not be related to radiotherapy, but rather may be explained by diagnostic bias, common etiologic factors, or by common pathway of carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, there is controversy whether radiotherapy for prostate cancer leads to an increased risk of bladder cancer. [8][9][10][11][12][13][14][15][16][17][18] In 2006, we first reported that bladder cancer patients who had received radiotherapy for prostate cancer had higher grade disease and presented at a higher stage than nonirradiated patients. 19 We now update our cohort and review the pathological features and survival outcomes of bladder cancer patients previously treated with or without radiotherapy for prostate cancer.…”
Section: Introductionmentioning
confidence: 99%